The Role of Wilayatul Hisbah in Enforcing Sharia Law (Study of Policy Implementation Based on Aceh Qanun Number 6 of 2014 Concerning Jinayat Law in Aceh Besar Regency) - Jalaluddin; Made Weni; Sri Hartini Jatmikowati (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2024)
Wilayatul Hisbah is expected to be able to carry out its role well in the implementation of Jinayat law policies in Aceh. The purpose of the study is to describe and analyze the role of Wilayatul Hisbah in enforcing sharia law in Aceh Besar Regency in accordance with Qanun Number 6 of 2014 concerning Jinayat Law and to describe and analyze various factors that become obstacles and drivers of Wilayatul Hisbah in enforcing sharia law in Aceh Besar Regency in accordance with Qanun Number 6 of 2014 concerning Jinayat Law. The research method used in this study is a qualitative method. Through qualitative methods, researchers want to gain an in-depth understanding and thinking about social reality and relevant facts related to the role of Wilayatul Hisbah. Data collection was carried out through observation and interviews, while the sources were determined by purposive sampling of 9 people. The results of the study show that the role of Wilayatul Hisbah in enforcing Sharia Law in Aceh Besar Regency based on Qanun Number 6 of 2014 concerning Jinayat Law has not been running well, both in terms of socialization, guidance and supervision. Public awareness is still very low and the limited number of PPNS investigator personnel and the vast area are obstacles for Wilayatul Hisbah personnel in carrying out their roles. The driving force in enforcing Sharia Law is related to regulations and the existence of budget and executive commitment. Related to the available budget is still very limited so that it becomes an obstacle in carrying out its role, as well as the government's responsibility is still on paper has not been realized in real terms with budget support and so far has only prioritized regulations alone.